Analyzing English language teacher candidates' assessment literacy: A case of Bruneian and Japanese universities. (December 2022) - Roslan, Roslinawati; Nishio, Yuri; Jawawi, Rosmawijah
Abstract: English language teacher candidates should possess Language Assessment Literacy (LAL) to help them determine the most suitable kinds of assessment for English language learners. This study investigated English language teacher candidates' preparedness for assessment responsibilities. Participants were 56 English language teacher candidates from Brunei and Japan studying in universities. A mixed-methods approach to data collection was taken involving questionnaires completed by the English language teacher candidates and interviews with a subset of 14 of the participants. The results from this study revealed that teacher candidates in both Brunei and Japan lacked sufficient knowledge of LAL, even though some of them possessed some teaching experience before entering their teacher education program. Implications for teacher training in English language (L2) contexts are discussed.